Synthesis and MASNMR characterization of VPI-5 molecular sieve - Venkatathri, N. (Asian Journal of Chemsitry, 2007)
The synthesized VPI-5 sample was characterized by XRD, SEM, FTIR, TG/DTA, Al-27, P-31 and 3Q MASNMR techniques, which shows that the sample was highly crystalline. Carbon and nitrogen analysis reveals that the sample contains no template molecules; however, TG/DTA analysis shows the presence of physisorbed template molecules. MASNMR results show the presence of two different types of aluminium and phosphorus, 3Q MASNMR shows the presence of two types of environmentally different tetrahedral aluminium, which are not observable by ordinary MASNMR along with known octahedral aluminium.
Keywords: 3Q-MASNMR; FTIR; MASNMR; SEM; synthesis; TG/DTA; VPI-5; XRD